Local Potential of Kabau (Archidendron bubalinum (Jack) I.C Nielsen): A Comprehensive Literature of Traditional Uses, Phytochemistry, Pharmacology and Learning Resources Potential - Erik Perdana Putra; Aceng Ruyani; Fitri April Yanti (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
Kabau (Archidendron bubalinum (Jack) I.C. Nielsen) is a lesser-known legume native to Sumatra and surrounding regions that is widely used as food and traditional medicine, but its scientific and educational potential remains underexplored. This study presents a qualitative–descriptive literature review synthesizing ethnobotanical, phytochemical, pharmacological, and educational evidence on kabau, based on peer-reviewed national and international publications indexed in databases such as Scopus, PubMed, SpringerLink, Wiley Online Library, and Google Scholar. The review shows that kabau seeds and fruit pods contain diverse secondary metabolites, dominated by phenolics, flavonoids, terpenoids, fatty acids (e.g., linoleic and palmitic acids), and sulfur-containing amino acids related to djenkolic acid. These constituents underpin strong in vitro antioxidant activity and support preliminary evidence of antidiabetic, anti-hyperuricemic, and antimicrobial effects in enzyme-based assays and animal models. Ethnobotanical data from Bengkulu and other regions document kabau as a functional food, a remedy for metabolic and digestive disorders, and a component of local cultural identity. Drawing on this evidence, the article proposes a framework for integrating kabau into biology education as a contextual learning resource across topics such as plant morphology, ecology, ethnobotany, phytochemistry, health, and STEM-based inquiry. Integrating local biological resources like kabau is argued to promote scientific literacy, critical thinking, and sustainability awareness while strengthening students’ appreciation of local biodiversity. Further field, experimental, and design-based research is needed to standardize kabau-derived products and to evaluate their effectiveness and safety, as well as their impact on learning outcomes in science education.